2018
DOI: 10.1016/j.mayocp.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race on the Incidence of Aortic Stenosis and Outcomes of Aortic Valve Replacement in the United States

Abstract: African Americans undergo AVR less than whites. The underlying etiology of this disparity is multifactorial, but may be related to a lower incidence of AS in AAs. Aortic valve replacement is associated with similar risk-adjusted in-hospital mortality but higher cost and longer hospitalizations in AAs than in whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 23 publications
4
37
0
Order By: Relevance
“…That said, there was no significant difference in aortic valve repairs/replacements in our study, and the aortic valve is the second most common valve affected by IE [18]. In another study using the NIS that compared aortic valve replacements in Black and White patients who presented with aortic stenosis, researchers found that Blacks were less likely to undergo surgery, as suggested by Alqahtani and Patel [9,19]. One potential reason the authors concluded for this finding was that Black patients are less likely to have severe aortic stenosis in general [19].…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…That said, there was no significant difference in aortic valve repairs/replacements in our study, and the aortic valve is the second most common valve affected by IE [18]. In another study using the NIS that compared aortic valve replacements in Black and White patients who presented with aortic stenosis, researchers found that Blacks were less likely to undergo surgery, as suggested by Alqahtani and Patel [9,19]. One potential reason the authors concluded for this finding was that Black patients are less likely to have severe aortic stenosis in general [19].…”
Section: Discussionmentioning
confidence: 41%
“…Additionally, valvular repairs/replacements are often indicated for patients who fail to respond appropriately to antimicrobials or develop significant complications from IE. However, prior studies have shown that Black patients receive less aortic and mitral valve repairs compared to White patients when such procedures are indicated [9,10]. Thus, determining if differences exist for in-hospital mortality and surgical interventions in older patients with IE by race is crucial to understanding potential aspects of care that need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…However, this could be due to some genetic difference in the occurrence of NRVHD, with less risk in blacks. Evidence to support this comes from the USA, where African Americans compared to Caucasians are at significantly lower risk of developing severe aortic stenosis due to degenerative calcific disease or congenitally bicuspid valve disease [82], as well as degenerative mitral valve disease presenting for surgery [83].…”
Section: Non-rheumatic Valvular Heart Diseasementioning
confidence: 99%
“…Although ethnicity, insurance status, income, and other socioeconomic factors were not discussed in the article by Zaouter et al, 1 racial and socioeconomic inequalities are welldocumented in the cardiac surgery literature. 5,6 Among valve surgery patients, African Americans tend to have longer and more costly hospital stays 7 and more frequent complications than their white counterparts. 8,9 Uninsured and Medicaid status, as markers of low socioeconomic position, are associated with increased postoperative mortality.…”
Section: Enhanced Recovery After Surgery Protocols May Help Reduce Ramentioning
confidence: 99%